Ideology and Political Ideas of Former Members of the Communist Party of Malaya Yala Province - Suphaphol, Suphachai; Wongsuwan, Kittinun (Ph.D. in Social Sciences Journal, 2026)
This research aims to examine the former members of the Malayan Communist Party (MCP) in Yala Province, Thailand, focusing on their political roles, ideologies, and perspectives. Additionally, it explores the history of the MCP and its political movement. The MCP was the third communist party to emerge in response to anti-colonial struggles, influenced by the Soviet Union in opposing Western colonial powers. The ideological conflict was a significant factor in the founding of the MCP and its political movement. However, this same conflict ultimately contributed to the party's collapse. The MCP sought to end the conflict, leading to their participation in the first negotiations, known as the 'Baling Talks,' which, however, were unsuccessful. Alongside the MCP's political structures, ideologies, and strategies, defectors and supporters also engaged in underground movements. These underground networks provided financial support, food, and weapons to sustain the jungle operations. Influenced heavily by the Communist parties of China and Vietnam, the MCP adopted operational tactics largely modeled on those used in China. Thus, the history of the MCP in Yala Province, along with their political movement, ideology, and beliefs, contributes to a deeper understanding of the anti-British colonial sentiment among the Chinese in the Malay Peninsula. The MCP operated with the objective of governing and protecting people in colonial territories from Western imperialism. Its origins and establishment differed significantly from modern political parties, which are bound by legal frameworks. The MCP was founded with a specific purpose and shared goal within the colonial context. Ultimately, the party was dissolved after signing a peace agreement as 'development partners' with Thailand."